Highly Aligned Graphene Aerogels for Multifunctional Composites - Wu, Ying; An, Chao; Guo, Yaru; Zong, Yangyang; Jiang, Naisheng; Zheng, Qingbin; Yu, Zhong‑Zhen (Nano-Micro Letters, 2024)
Stemming from the unique in-plane honeycomb lattice structure and the sp2 hybridized carbon atoms bonded by exceptionally strong carbon–carbon bonds, graphene exhibits remarkable anisotropic electrical, mechanical, and thermal properties. To maximize the utilization of graphene's in-plane properties, pre-constructed and aligned structures, such as oriented aerogels, films, and fibers, have been designed. The unique combination of aligned structure, high surface area, excellent electrical conductivity, mechanical stability, thermal conductivity, and porous nature of highly aligned graphene aerogels allows for tailored and enhanced performance in specific directions, enabling advancements in diverse fields. This review provides a comprehensive overview of recent advances in highly aligned graphene aerogels and their composites. It highlights the fabrication methods of aligned graphene aerogels and the optimization of alignment which can be estimated both qualitatively and quantitatively. The oriented scaffolds endow graphene aerogels and their composites with anisotropic properties, showing enhanced electrical, mechanical, and thermal properties along the alignment at the sacrifice of the perpendicular direction. This review showcases remarkable properties and applications of aligned graphene aerogels and their composites, such as their suitability for electronics, environmental applications, thermal management, and energy storage. Challenges and potential opportunities are proposed to offer new insights into prospects of this material. Highlights: 1 Aligned graphene building blocks take full advantages of the outstanding properties of graphene. 2 Comprehensive review of recent advancements in the utilization of highly aligned graphene aerogels for multifunctional applications. 3 By systematically summarizing the controlled assembly, aligned structural attributes, quantitative characterization methods, anisotropic properties, and multifunctional applications of graphene aerogels, this review enhances understanding of the material's potential for diverse applications, offering tailored properties and novel functionalities.